The LCD = 6x^2y^3 ( because LCD of 3 and 6 = 6, LCD of x^2 and x = x^2 and LCD of y and y^3 = y^3)
now divide 3x^2y into the LCD then multiply this by 5 to get the first term in the numerator and do similar process to get second term, so we get:-
5(2y^2) - 4(x)
------------------
6x^2y^3
= 2( 5y^2 - 2x)
-----------------
6x^2y^3
= 5y^2 - 2x
-----------
3x^2y^3
Answer:
-5/7
Step-by-step explanation:
(-4,2) (3,-3)
-3-2= -5
3-(-4)= 7
-5/7
Step-by-step explanation:
3 answer.....
......dkdkdk
It has orders and equally distanced value between units , the zero point characteristic makes it relevant or meaningful to say “ one object has twice the length of the other “ example
4:3 is a ratio